Physiotherapy treatement of patients with perinatal brachial plexus injury - Anna Lewandowska; Dorota Ratuszek-Sadowska; Monika Kuczma; Waldemar Kuczma; Mikołaj Kurczewski; Wojciech Hagner (Kazimierz Wielki University, 2018)
Perinatal brachial plexus injury are usually a consequence of shoulder dystocia during childbirth, after the birth of the head there are difficulties with the birth of the shoulders. In this situation, childbirth is stopped and the shoulders of the fetus are not born spontaneously. The development of medicine provides patients with access to many methods of treating this injury. An interdisciplinary team of specialists is needed to minimize the negative effects of damage that are perceived by the patient, sometimes throughout life. Knowledge about physiotherapy in perinatal damage of the shoulder plexus is of great importance for the future of a child who suffered perinatal trauma to the shoulder plexus. Therefore, this topic should be constantly developed and re-examined so that in the future we can provide patients with multi-specialist care.